Ivan Prijatelj in ruska literatura - Zadravec, Franc (Slavistična revija, 2005)
Ivan Prijatelj represents a logical pinnacle and first scholarly successful conclusion of several decades of Slovene surveys of Russian literature. As he wrote about Russian authors for forty years, one justifiably wonders what, besides academic curriculum, compelled him to return to them with such persistence. The main goal of this article is to answer this question.
Keywords: literarna kritika; literarni zgodovinarji; literary criticism; literary historian; Prijatelj, Ivan, 1875-1937; ruska književnost; Russian literature; Slovene literature; slovenska književnost